In Silico Study of Gamma-Mangostin Compound from Garcinia Mangostana L. Fruit Skin and Activity Test as an Alpha Amylase Inhibitor - Kurniawan, Kurniawan; Marfu'ah, Nurul; Fazriah D., Gita (Journal La Medihealtico, 2025)
The aim of this study is to determine the interaction between the gamma-mangostin compound and the α-amylase enzyme using molecular docking modeling and in vitro. The results of molecular docking showed that all compounds could interact with the active site of the α-amylase enzyme. The gamma-mangostin compound has a fairly negative binding affinity. The binding affinity score of the compound was then compared with the control, namely the carbohydrate inhibitor acarbose. The results showed that the binding affinity quite close to the control, namely -9.1 kcal/mol, while the control was -16.4 kcal/mol, but the score was not negative enough. Interaction of the target protein with the alpha amylase compound to determine the amino acid residues on the active side of the protein. The results showed that there were hydrogen, alkyl and van der waals bonds on the active side of the protein that were the same as the control. In silico and in vitro, the gamma-mangostin compound has the potential to reduce blood sugar levels with an α-amylase inhibitor, in vitro with percentage of 43.33% approaching the positive control, namely acarbose, which is 56.25% at a concentration of 200 ppm and an IC50 value of 166.06 ppm.